A need to implement new tools for diagnosing tobacco-addition syndrome and readiness/motivation to quit smoking in the working-age population in Poland - Marzenna Broszkiewicz; Wojciech Drygas (Nofer Institute of Occupational Medicine, 2016)
High rates of tobacco use is still observed in working-age population in Poland. The present level of the state tobacco control has been achieved through adopting legal regulations and population-based interventions. In Poland a sufficient contribution of health professionals to the diagnosis of the tobacco-addition syndrome (TAS) and the application of the 5A's (ask, advice, assess, assist, arrange follow-up) brief intervention, has not been confirmed by explicit research results. Systemic solutions of the health care system of the professional control, specialist health care, health professional trainings and reference centres have not as yet been elaborated. The tools for diagnosing tobacco dependence and motivation to quit smoking, developed over 30 years ago and recommended by experts to be used in clinical and research practice, have not met the current addiction criteria. In this paper other tools than those previously recommended − tests developed in the first decade of the 21st century (including Cigarette Dependence Scale and Nicotine Dependence Syndrome Scale), reflecting modern concepts of nicotine dependence are presented. In the literature on the readiness/motivation to change health behaviors, a new approach dominates. The motivational interviewing (MI) by Miller and Rollnick concentrates on a smoking person and his or her internal motivation. Motivational interviewing is recommended by the World Health Organization as a 5R's (relevance, risks, rewards, roadblocks, repetition) brief motivational advice, addressed to tobacco users who are unwilling to make a quit attempt. In Poland new research studies on the implementation of new diagnostic tools and updating of binding guidelines should be undertaken, to strengthen primary health care in treating tobacco dependence, and to incorporate MI and 5R's into trainings in TAS diagnosing and treating addressed to health professionals. Med Pr 2016;67(1):97-108